Heterogeneous Firms, the Structure of Industry & Trade under Oligopoly - Eddy Bekkers; Joseph Francis Francois (Johannes Kepler University of Linz, Department of Economics, 2008)
We develop a model with endogeneity in key features of industrial structure linked to heterogeneous cost structures under Cournot competition. We use the model to explore issues related to cross-country differences in industry structure and the impact of globalization on markups and pricing, concentration, and productivity. The model nests two workhorse trade models, the Brander & Krugman reciprocal dumping model and the Ricardian technology-based trade model, as special cases. We examine both free entry and limited entry (free exit) cases. The model generates clear testable predictions on the probability of zero trade flows and the pattern of export prices, and on cross-country and industry variations in industrial structure controlling for openness. Market prices decline as a result of trade liberalization, the least productive firms get squeezed out of the market, exporting firms gain market share, and more firms become trade oriented. In addition, depending on the strength of underlying cost heterogeneity, falling prices are consistent with both increasing and falling industry concentration following episodes of integration. Welfare rises with trade liberalization, unless trade costs decline from a prohibitive level in the short run free exit case. Variation across industries and markets in markups, concentration, and pricing structures is otherwise a function of market size and the variation in cost heterogeneity across industries.
Keywords: L11; L13; F12; 330; Firm heterogeneity; Cournot competition; Composition effects of trade liberalization; Industriestruktur; Duopol; Außenhandelsliberalisierung; Markteintritt; Wohlfahrtsanalyse; Theorie